(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Sklyarova N.G., Nikolaeva A.V., Simonova K.N. This article is devoted to the review of the International linguistic Crimean Congress "Language and the World" in Yalta in the autumn of 2012. The purpose of this event is to integrate people working in the area of education and science, to share experience, discuss the results of research and teaching programs and projects. In the focus of the congress were such global problems as the functional description of natural language and its units; geolinguisics and linguistic worlds; linguistic instrumentology and others. Keywords: association, experience, teaching, geolinguistics, scientific problems.